تحليل مادة كتاب الدرس دروس اللغة العربية الجزء الأول تأليف إمام زَركشى و إمام شُبانى فى الفصل السابع بمعهد الرّوضة الحسنة - andi setiawan; Firmansyah Firmansyah (Jurnal Al-Hibru, 2024)
The purpose of this study is to determine the quality of the book Durusul Lughah Al Arabiyah Volume 1 by Imam Zarkasyi and Imam Syubani in terms of material, presentation, and to find out the advantages and disadvantages of the book. This research is a library research. Data was obtained using documentation techniques, in the form of journals, books, articles, and certain writings by using content analysis in analyzing the data. The result of this study is that the material in the book Durusul Lughah Al Arabiyah Volume 1 is good and in accordance with the standard book, consisting of 25 chapters that cover daily activities along with examples of pictures, vocabulary, linguistic rules and questions so as to make it easier for learners, especially beginners in learning, understanding and practicing Arabic in daily conversation. And the shortcomings of the book Durusul Lughah Al Arabiyah Volume 1 by Imam Zarkasyi and Imam Syubani are in terms of the lack of color pictures in mufrodat, table of contents, bibliography, muhadasah, nahu shorofnya. But basically this book has met the criteria as seen from the successful use of this book in learning Arabic in Islamic boarding schools and religious schools.